IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN PREPARING THE 21ST CENTURY GENERATION TO WELCOME THE ERA OF SOCIETY 5.0 - Jayadi, Jayadi; Marini, Arita; MS, Zulela (PD PGMI se Indonesia, 2023)
Society 5.0 is a society that can solve various social challenges and problems by utilizing various innovations born in the era of the Industrial Revolution 4.0, such as the Internet of Things, Artificial Intelligence, Big Data (large amounts of data), and robots to improve the quality of human life. This era is a new opportunity and a challenge for students to enhance soft skills in preparation for the future. The curriculum is the